Discourse Analysis of Merdeka Belajar Curriculum Application in Madrasahs toward the Islamic Religious Education Learning System - Muhammad Muhson (EDUCATIO: Journal of Education)
There is a paradigm shift in learning in the 21st century and in order to improve the quality of services for madrasah residents, madrasahs must always make adjustments and improvements, dare to innovate or make new discoveries by utilizing information technology to the fullest. Madrasahs must be free to manage education independently, creatively, innovatively in order to provide services that take into account the needs of society and the advancement of science and technology.  Decree of the Minister of Religious Affairs Number 792 of 2018 concerning Guidelines for the Implementation of the Raudhatul Athfal Curriculum, Decree of the Minister of Religion Number 183 of 2019 concerning the Curriculum of Islamic Religious Education and Arabic in madrasas, and Decree of the Minister of Religion Number 184 of 2019 concerning Guidelines for Curriculum Implementation in madrasas, provides space for madrasahs to create and innovate in the management of education and learning.  In line with this, the Ministry of Education, Culture, Research and Technology has launched the Independent Curriculum which will be implemented starting from the 2022/2023 academic year.  This research method uses a qualitative approach. Data collection through the literature method (search library) through books, journals and articles that support the explanation of the application of the independent curriculum in Madrasah.   The advantages of the Independent Curriculum are simpler and deeper, autonomous, more relevant, and participatory.  The learning objectives of PAI and Ethics (1) guiding students to be moral (2) shaping students into human beings who understand the principles of the Islamic religion (3) teaching students how to apply Islamic principles (4) helping students develop love for their surroundings (5) building ukhuwwah basyariyah, ukhuwwah Islamiyah, and ukhuwwah waaniyyah. The characteristics of CP PAI and Ethics must be based on the Qur'an-Hadith, aqidah, akhlak, fiqh, and the history of Islamic Civilization (SPI).  The weaknesses of the Merdeka Belajar Curriculum include that students' abilities and skills are not seen as knowledge that sustains it because Askomi Suka (Minimum Competency Assessment and Character Survey) only focuses on personality and character.  Rpp is less discernible because it is not detected by the indicators, including the media, equipment, and learning resources used. Another drawback is the absence of output that can be evaluated due to time constraints over a long period of time.